The Effect of Social Connectedness on Crime: Evidence from the Great Migration - Bryan Stuart; Evan J. Taylor (Institute of Labor Economics (IZA), 2019)
This paper estimates the effect of social connectedness on crime across U.S. cities from 1970 to 2009. Migration networks among African Americans from the South generated variation across destinations in the concentration of migrants from the same birth town. Using this novel source of variation, we find that social connectedness considerably reduces murders, rapes, robberies, assaults, burglaries, and motor vehicle thefts, with a one standard deviation increase in social connectedness reducing murders by 21 percent and motor vehicle thefts by 20 percent. Social connectedness especially reduces murders of adolescents and young adults committed during gang and drug activity.
Keywords: K42; N32; R23; Z13; 330; crime; social connectedness; Great Migration